Dinamika Pendapatan Tiket Penerbangan Domestik PT Garuda Indonesia Tbk - Saifuloh, Nur Imam; Panggabean, Bungaran; Butarbutar, Sopar Tumpak Rensius (Jurnal Manajemen Dirgantara, 2025)
The main revenue of service companies engaged in the aviation industry comes from the sale of passenger tickets, and PT Garuda Indonesia Tbk is no exception. However, there was a drastic decline when the covid-19 pandemic hit which limited the mobility of people. This study is directed at comparing pre- and post-pandemic conditions, which will then lead to an analysis of domestic flight ticket revenue factors. A quantitative approach is used to dissect the problem with paired sample t-test and exploratory factor analysis (EFA). The initial test uses secondary data in the form of pre- and post-pandemic airplane ticket revenues for each of the 15 periods (months). Meanwhile, the second test used primary data collected through distributing questionnaires to 60 respondents who use economy aircraft type B737-800NG on domestic routes. The results showed a significant difference in pre and post-pandemic airplane ticket revenues. After an in-depth study, of the six proposed determinant variables, two of them can be considered as determinants, namely maintenance as factor 1 and price as factor 2. The remaining four variables, namely punctuality, audio video services, aircraft cleanliness and seat comfort, are categorized in factor 1. These findings support the importance of airline marketing strategies, especially setting competitive ticket prices and excellent service to its users. The more affordable the price offered plus the better the service. The practical implications for management are (1) operational efficiency such as aircraft fleet optimization or digitization and automation of business processes, (2) product and service segmentation by offering tiered services and ticket bundling, (3) utilization of technology by opening application-based services and loyalty programs, (4) strategic partnerships, especially hotels, restaurants and land transportation, and (5) focus on customer satisfaction.